Nanoengineered targeting strategy for cancer immunotherapy - Yin Wei-min; Li Yu-wei; Gu Yun-qing; Luo Min (Acta Pharmacologica Sinica, 2020)
Cancer immunotherapy is rapidly changing the paradigm of cancer care and treatment by evoking host immunity to kill cancer cells. As clinical approval of checkpoint inhibitors (e.g., ipilimumab and pembrolizumab) has been accelerated by a dramatic improvement of long-term survival in a small subset of patients compared to conventional chemotherapy, growing interesting research has focused on immunotherapy. However, majority of patients have not benefited from checkpoint therapies that only partially remove the inhibition of T cell functions. Insufficient systemic T cell responses, low immunogenicity and the immunosuppressive environment of tumors, create great challenges on therapeutic efficiency. Nanotechnology can integrate multiple functions within controlled size and shape, and has been explored as a unique avenue for the development of cancer immunotherapy. In this review, we mainly address how nanoengineered vaccines can induce robust T cell responses against tumors, as well as how nanomedicine can remodel the tumor immunosuppressive microenvironment to boost antitumor immune responses.